REPRESENTASI IDEOLOGI NEGARA DALAM BUKU TEKS SEJARAH - Indah Wahyu Puji Utami (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2014)
History lesson is a medium to embed state ideological discourse. One of the instruments used in this practice is a history textbook. History textbooks written based on the curriculum set by the state as part of the official history. History textbooks represent various state ideology such as, constitutionalism, anti-communism, stability, development, democracy, anti- New Order and economic globalization. Keywords: history, textbooks, representation, ideology